2012
DOI: 10.1371/journal.pone.0050001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Conserved and Novel microRNAs in Cashmere Goat Skin by Deep Sequencing

Abstract: MicroRNAs (miRNAs) are a class of small RNAs that play significant roles in regulating the expression of the post-transcriptional skin and hair follicle gene. In recent years, extensive studies on these microRNAs have been carried out in mammals such as mice, rats, pigs and cattle. By comparison, the number of microRNAs that have been identified in goats is relatively low; and in particular, the miRNAs associated with the processes of skin and hair follicle development remain largely unknown. In this study, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Liu et al identified the miRNAs in goat skin by Deep Sequencing (Liu et al 2012). They found that 68 miRNAs were conserved in goat and had been reported in NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al identified the miRNAs in goat skin by Deep Sequencing (Liu et al 2012). They found that 68 miRNAs were conserved in goat and had been reported in NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…With the successful applications of high-throughput sequencing technologies, a large number of miRNAs regulating the development of the mammary glands, skin growth, and the hair follicle formation cycle have been identified in goats [1820]. However, the number of goat miRNA sequences in miRBase is much lower compared to the data deposition of miRNAs for pig and cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The miR-184 inhibition argonaute 2 protein expression [22] and the growth of hair follicles [23]. And miRNA-199b has an important role in skin and hair follicle development [24,25]. The miR-1623 target genes that played important roles in Wnt/β-catenin pathway [19].…”
Section: Discussionmentioning
confidence: 99%